A minimalistic approach to identify substrate binding features in B1 Metallo-β-lactamases - Poeylaut Palena, Andrés Alberto (2007)
The 2-oxoazetidinylacetate sodium salt was synthesized as a model of a minimal β-lactam drug. This compound and the monobactam aztreonam were assayed as substrates of the Metallo-β-lactamase BcII. None of them was hydrolyzed by the enzyme. While the azetidinone was not able to bind BcII, aztreonam was shown to bind in a nonproductive mode. These results provide an explanation for the unability of Metallo-β-lactamases to inactive monobactams and give some clues for inhibitor design.